2021
DOI: 10.3389/fgene.2021.702889
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM Gene Family Mutations Associated With Inherited Breast Cancer Risk – A Comparative Oncology Approach to Discovery

Abstract: IntroductionRecent studies comparing canine mammary tumors (CMTs) and human breast cancers have revealed remarkable tumor similarities, identifying shared expression profiles and acquired mutations. CMTs can also provide a model of inherited breast cancer susceptibility in humans; thus, we investigated breed-specific whole genome sequencing (WGS) data in search for novel CMT risk factors that could subsequently explain inherited breast cancer risk in humans.MethodsWGS was carried out on five CMT-affected Gold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…We unexpectedly observed that some genes of the CEACAM family, markers of cancer progression in many solid malignancies [14], were downregulated in MCF-7pR cells (Figure 2a). Our findings seem to corroborate previous results in which CEACAM loss of heterozygosity (LOH) or truncating mutations were associated with tumorigenesis and metastasis in breast cancer [15,16], although this hypothesis needs further study. We also found that pro-apoptotic genes, such as CASP3 and PYCARD, are downregulated in MCF-7pR, whereas the pro-survival BCL2 gene is strongly upregulated (Log2FC = 3.1, padj = 1.15 × 10 −169 ; Figure 2a,b), suggesting an imbalance of cell death/survival stimuli in favor of the latter.…”
Section: Pathway Analysis Of Palbociclib-resistant Cellssupporting
confidence: 90%
“…We unexpectedly observed that some genes of the CEACAM family, markers of cancer progression in many solid malignancies [14], were downregulated in MCF-7pR cells (Figure 2a). Our findings seem to corroborate previous results in which CEACAM loss of heterozygosity (LOH) or truncating mutations were associated with tumorigenesis and metastasis in breast cancer [15,16], although this hypothesis needs further study. We also found that pro-apoptotic genes, such as CASP3 and PYCARD, are downregulated in MCF-7pR, whereas the pro-survival BCL2 gene is strongly upregulated (Log2FC = 3.1, padj = 1.15 × 10 −169 ; Figure 2a,b), suggesting an imbalance of cell death/survival stimuli in favor of the latter.…”
Section: Pathway Analysis Of Palbociclib-resistant Cellssupporting
confidence: 90%
“…Upon surveying the CEACAM gene family for rare PTVs and missense variants in CRC cases from TCGA and controls from the EVS, no gene-based or gene family-based associations with inherited risk of CRC were revealed. These results were unexpected due to the previous association of rare PTVs in the CEACAM gene family with inherited breast cancer risk [ 16 ], the known similarities between breast cancer and CRC risk [ 1 , 17 , 18 ], and the dis-regulation of CEACAM genes in CRC tumors [ 6 , 8 15 ]. Moreover, it has been demonstrated that CEACAM gene function can be affected by even minor genetic changes [ 27 ], and specific residues within CEACAM proteins are crucial for normal function [ 12 , 30 , 31 ].…”
Section: Main Textmentioning
confidence: 97%
“…Despite the lack of association from aggregation analyses, individual variants were associated with CRC inherited risk (Tables 1 and 2 ). All associations involved individual missense variants; none involved PTVs, unlike the association of CEACAM PTVs with breast cancer risk [ 16 ]. Only four different PTVs were detected amongst all CRC cases, none of which overlapped between ethnicities.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that breast cancer is becoming one of the malignant diseases with high incidence in the world, accounting for about 12% in all kinds of female cancers [1] , and data demonstrated that 5-10% of breast cancer is hereditary because of genetic susceptibility [2,3] . up to now, the genes found susceptible to breast cancer account for 25-30% in hereditary breast cancers [4] ; interestingly, a large number of patients with breast cancer family history do not carry risk variations in these genes, indicating that there may be other genetic risk factors [5] .…”
Section: Introductionmentioning
confidence: 99%